Supraphysiological Concentrations of Bisphenol A Alter the Expression of Extracellular Vesicle-Enriched miRNAs From Human Primary Granulosa Cells. (28th January 2019) - Rodosthenous, Rodosthenis S; Baccarelli, Andrea A; Mansour, Abdallah; Adir, Michal; Israel, Ariel; Racowsky, Catherine; Hauser, Russ; Bollati, Valentina; Machtinger, Ronit
Abstract: Bisphenol A (BPA) is a widely used chemical that has been detected in follicular fluid and associated with adverse reproductive effects. Granulosa cells have an important role in follicular growth and oocyte maturation, however, little is known about the biological mechanisms of BPA toxicity on human granulosa cells. In this study, we exposed primary granulosa cells to different concentrations of BPA (0, 20, 200, 2000, and 20 000 ng/ml) and used quantitative polymerase chain reaction to measure the expression levels of miRNAs enriched in extracellular vesicles (EV-enriched miRNAs), and cellular levels of selected target genes of differentially expressed EV-enriched miRNAs. We found that exposure to 20 000 ng/ml BPA was associated with decreased levels of EV-miR-27b-3p (FC = 0.58, p  = .04) and increased levels of its biologically relevant target genes FADD (FC = 1.22, p  = .01), IGF1 (FC = 1.59, p  = .06), and PPARG (FC = 1.73, p  = .001) as compared with the control. In addition, we observed that under the same exposure conditions, the expression levels of miR-27b-3p in granulosa cells were also downregulated (FC = 0.65, p  = .03) as compared with the control. Our findings suggest that both cellular and extracellular changes in gene expression may mediate BPA toxicity in granulosa cells.